LEVELING CHARACTERISTICS INTERCONNECTION BETWEEN PERSONALITY COMPETITIVENESS AND SUBJECTIVE WELL-BEING OF HIGH SCHOOL STUDENTS - E E Bocharova (Peoples' Friendship University of Russia (RUDN University), 2016)
The paper presents the theoretical and empirical study of the relationship of personality characteristics of level of competitiveness and subjective well-being. The study was performed on a sample of high school students ( N = 70, female and male; 16-17 years old), differing in the level of personal competitiveness, with psycho-diagnostic tools, "Express-diagnostics of personal competitiveness"(G.M. Manuilov), "Express-diagnostics of the level of social frustration (L. Wasserman)", "The scale of subjective well-being" (M.V. Sokolova), "My self-regulation of behavior and activity" (V.I. Morosanova). It is shown that the ability for self-education, self-improvement, self-planning and modeling their prospects, achieving the goal on the background of their satisfaction with relations with the immediate environment acts as a basic capacity for personality competition in adolescents. The applied aspect of the research problem can be implemented in the development of programs of psycho- pedagogical support of the formation and development of personal competitiveness of students.